2007
DOI: 10.1523/jneurosci.3886-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Changes in Cortical Surface Potentials during Motor Movement

Abstract: In the first large study of its kind, we quantified changes in electrocorticographic signals associated with motor movement across 22 subjects with subdural electrode arrays placed for identification of seizure foci. Patients underwent a 5-7 d monitoring period with array placement, before seizure focus resection, and during this time they participated in the study. An interval-based motor-repetition task produced consistent and quantifiable spectral shifts that were mapped on a Talairach-standardized template… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

113
644
3
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 692 publications
(761 citation statements)
references
References 46 publications
113
644
3
1
Order By: Relevance
“…The additional variance in BOLD explained by low frequencies was not restricted to primary areas, suggesting that low frequencies are related to more distributed BOLD changes. Consistent with previous studies [Crone et al, 1998b;Lachaux et al, 2006;Miller et al, 2007], low frequency power decreases were spatially more distributed than high frequency power increases. Understanding how different processes reflected in the LFP are integrated in fMRI activation maps is essential to link fMRI findings to both noninvasive EEG and MEG experiments that measure neuronal signals over larger areas of cortex and invasive studies in nonhuman primates that extract neuronal signals from small areas of cortex.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The additional variance in BOLD explained by low frequencies was not restricted to primary areas, suggesting that low frequencies are related to more distributed BOLD changes. Consistent with previous studies [Crone et al, 1998b;Lachaux et al, 2006;Miller et al, 2007], low frequency power decreases were spatially more distributed than high frequency power increases. Understanding how different processes reflected in the LFP are integrated in fMRI activation maps is essential to link fMRI findings to both noninvasive EEG and MEG experiments that measure neuronal signals over larger areas of cortex and invasive studies in nonhuman primates that extract neuronal signals from small areas of cortex.…”
Section: Discussionsupporting
confidence: 91%
“…Increases in HFB change were focused on primary sensorimotor electrodes during movement (Figs. 1, 2, and 5), consistent with previous studies [Crone et al, 1998a;Leuthardt et al, 2007;Miller et al, 2007;Miller et al, 2009b]. This high frequency spectral power change has been shown to correlate directly with firing rate [Manning et al, 2009;Miller et al, 2009a;Whittingstall and Logothetis, 2009], and has been demonstrated to reflect broadspectral change across all frequencies Miller et al, 2009b].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Mu/beta (10-30 Hz) is a motor rhythm that broadly decreases in power over motor areas in response to movement or imagined movement (21). In contrast, power in the high-gamma (70-100 Hz) band increases very locally in response to specific motor movement or imagery (22). Both signals have been successfully used for BCI control (23)(24)(25).…”
Section: Resultsmentioning
confidence: 99%
“…We also tested and did not find any evidence for significant correlation with other frequency bands (i.e. ÎŽ = 1–4 Hz, Ξ = 4–8 Hz, α = 8–12 Hz, ÎČ = 18–26 Hz, low Îł = 30–50 Hz11, 12, 13). …”
Section: Resultsmentioning
confidence: 89%